Corporate Social Responsibility and Psychosocial Risk Management in Europe - Jain, Aditya; Leka, Stavroula; Zwetsloot, Gerard (2011)
Corporate social responsibility (CSR) is a comprehensive concept that aims at the promotion of responsible business practices closely linked to the strategy of enterprises. Although there is no single accepted definition of CSR, it remains an inspiring, challenging and strategic development that is becoming an increasingly important priority for companies of all sizes and types, particularly in Europe. Promotion of well-being at work is an essential component of CSR; however, the link between CSR, working conditions and work organisation is still found to be unfamiliar to stakeholders. As CSR is strategic and is regarded by many companies and corporate leaders as an important development, it offers opportunities for psychosocial risk management, an area that is currently among the top priorities in working environment and well-being at work debates. However, the link between CSR and psychosocial risk management has not been addressed clearly before. This paper aims to explore the potential role of CSR in promoting well-being at work through the development of a framework for the management of psychosocial risks. As part of the research, key stakeholders [including the World Health Organization (WHO), the International Labour Organization (ILO), the European Agency for Safety and Health at Work (EU-OSHA), the European Commission (EC), employers’ associations, trade unions and other policy experts] across Europe participated in a survey, interviews and focus groups to assess and clarify the link between CSR and psychosocial risk management. On the basis of the findings, a CSR-inspired approach to the management of psychosocial issues at work is proposed. Such an approach can be a useful tool in contexts where, up until now, expertise and tradition in dealing with psychosocial issues have been lacking.
Keywords: Europe; Well-being; work-related stress; CSR; psychosocial risk management